Gap Analysis of Risk Management Process Based on ISO 31000:2018 at Industrial Plantation Forest Company PT.XYZ - Prasetyo, Tasya Regita; D.Djakman, Chaerul (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p16, 2025)
HTI business is a long-term business. However, PT.XYZ has not implemented risk management standards in its business even though the company's performance has declined in recent years and plans to adopt risk management standards. With gap analysis, the company can find out the gaps in the risk management process that should use the ISO 31000:2018 standard. Thus, the company can improve company performance through continuous improvement in increasing the efficiency and effectiveness of the company. This study aims to analyze the gaps in the risk management process at PT.XYZ according to ISO 31000:2018. The research approach uses a qualitative method with a case study type. The results of the study show that the gap in the implementation of the PT.XYZ risk management process which includes the process of identification, analysis, evaluation, and risk treatment has not been carried out systematically and documented. Keywords: Industrial Tree Plantation; Gap Analysis; Risk Management; ISO 31000:2018.